Pola Resistensi Kuman Mycobacterium tuberculosis Terhadap Obat Anti Tuberkulosis (OAT) di Propinsi Daerah Istimewa Yogyakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
ABSTRACT Tuberculosis (TB) remains the major public health problem worldwide, including Indonesia. To control the epidemic chain, TB patients need to be treated Anti-tuberculosis drugs (OAT). Improper medication leads to the resistance of one or more OAT regimen used for tuberculosis treatment. Resistance to OAT becomes the major problem in the treatment and control of tuberculosis infection chain. This research is aimed to describe the M. tuberculosis resistance to OAT, to analyze factors related to the resistance and sputum conversion at the end of the intensive phase, as well as to analyze the relation between M. tuberculosis OAT resistance and sputum conversion at the end of the intensive phase. The study was conducted in Yogyakarta Province during the period July - October 2002. Tuberculosis patient over 15 years old with positive acid-fast bacilli (BTA) test in two or more sputum specimen were recruited in the health services. M. tuberculosis resistance test to INH, rifampicin, etambutol, and streptomycin were conducted in-vitro. Sputum conversion examination was done at the end of the intensive phase (the end of 2nd month of treatment). Factors such as nutritional status, disease history, contact history and treatment history were identifiecUisng questionnare. Univariate and bivariate statistical analysis were conducted. -The resistance pattern of M.tuberculosis in Yogyakarta Province during July - October 2002 showed 61,35% patient resistance to INH, 46,2% to streptomycin and 30,8% to etambutol. No resistance to rifampicin was observed. A significant relationship was observed between the M. tuberculosis resistance to OAT and sputum conversion at the end of the intensive phase (p=0,000). It was concluded that the resistance pattern in Yogyakarta was dominated by resistance of M. tuberculosis to INH. No case of multiple drug resistance was identified in this study M. tuberculosis resistance to OAT was significantly related to the sputum conversion at the end af the intensive phase.